Normativna ureditev in preventivna dejavnost na področju nasilja v družini v Sloveniji - Pogorevc, Jovita (Sodobna pedagogika, 2024)
In the paper is fist presented starting points for the development of legislative frameworks in the field of domestic violence in Slovenia and presented the importance of treatment by individual institutions. At the same time is recognised the important role of preventive activity in this area and presented an example of regional implementation within the Centre for Social Work South Primorska. We find that such activities need to be systematically and continuously included in various target groups of people, and especially in educational institutions. There are also exposed some of the shortcomings in the area of domestic violence relating to the collection of data in the studied area, between institutions, that are dealing with this issue unrelated.
Keywords: center za socialno delo; centre for social work; domestic violence; education; nasilje v družini; pedagogika; pedagogy; regulations; vzgoja in izobraževanje; zakonodaja